Anti‐Stokes signal conversion of femtosecond pulses at near‐ultraviolet wavelength in photonic crystal fibre. Issue 21 (1st October 2013) - Yuan, Jinhui; Zhou, Guiyao; Liu, Hongzhan; Xia, Changming; Sang, Xinzhu; Wu, Qiang; Yu, Chongxiu; Wang, Kuiru; Yan, Binbin; Han, Ying; Farrell, G.; Hou, Lantian
Abstract : Anti‐Stokes signals at the near‐ultraviolet wavelength are efficiently generated based on degenerate four‐wave mixing by coupling the femtosecond pulses into the fundamental mode of a photonic crystal fibre. When the pump pulses with the central wavelength of 840 nm and the average power of 300 mW are used, the conversion efficiency η s of the anti‐Stokes signal at 432 nm can be up to 40℅, and the pulse width is measured to be 42 fs by the Talbot effect.